PENGUMPULAN DATA PERSEBARAN PIK-R MENGGUNAKAN OPEN DATA KIT (ODK) DI PROVINSI SUMATERA BARAT - Yezil Mulfarrizi (JURNAL BUANA, 2025)
This research aims to collect the distribution of pik-r in West Sumatra Province. The research method used was descriptive research with a qualitative approach. primary data obtained from direct observation at the research location. The results of this research are a map of the distribution of PIK-R in West Sumatra Province using an open data kit with the results of very minimal use of PIK-R in West Sumatra, this is because more students who contact PIK R tend to use messaging applications rather than face to face.